Production Of Organic Acids From Restaurant Wastes As Substrates For Polyhydroxybutyrate Production By Recombinant E. Coli - Eshtaya, Majd Khalid (2007)

(untitled)
In this study, restaurant waste was utilized as sole carbon source for the production of polyhydroxybutyrate (PHB) by recombinant Escherichia coli. PHB production was achieved via a two-stage process; organic acids production from fermented restaurant waste followed by PHB production utilizing the organic acids. In the first stage, the effect of initial pH, operating temperature and enzymatic pretreatment (hydrolysis using α-amylase and glucoamylase) were investigated to get highest organic acids production from restaurant wastes in anaerobic treatment. Anaerobic treatment was carried out in 500 mL Erlenmeyer flask using orbital shaking incubator. Three different temperatures were chosen; 30°C, 37°C and uncontrolled (room temperature). The initial pH of fermentation was also varied; adjusted at 7 and without adjustment. The organic acids produced were maximum (66 g/L) on the fifth day of fermentation that was carried out at 37°C, initial pH adjustment at 7 and enzymatic pretreatment with the yield of 0.723 g organic acids/g initial COD. The main organic acids produced was acetic acid (50%),followed by lactic acid (33%), iso-butyric acid (9%) and n-butyric acids (8%). The results indicate that high concentration of organic acids were produced in anaerobic treatment of restaurant wastes, which could served as alternative and abundant substrate for the production of biodegradable plastics. The supernatant collected from the anaerobic treatment of highest organic acids production was concentrated by vacuum evaporation to be used for PHB production. The total organic acids obtained after evaporation process was about 100 g/L. In the second stage, the concentrated organic acids were successfully converted to PHB using batch and pH-stat fed-batch fermentation by recombinant Escherichia coli containing. In batch fermentation about 6.8 g/L of cell dry weight and 2.5 g/L of PHB were achieved after 18 hours of cultivation, resulting in PHB content of 36% and productivity of PHB 0.14 g L-1 h-1. On the other hand, the maximum PHB concentration obtained was 9.2 g/L after 17 hours corresponding to 44% (g/g) of PHB content and 0.539 g L-1 h-1 productivity in pH-stat fed-batch fermentation.